Strategies of English Lecturers in Facilitating Interactional Communication of English Students During the New Normal Period of the Covid 19 Pandemic at UIN Fatmawati Sukarno Bengkulu for the 2021-2022 Academic Year - Ferri Susanto; Patricia Pérez Ramos; Muhammad Abdul Ali Sayyid Ibrahim (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
This research aims to describe the strategy of English lecturers in facilitating interactional communication of English students at the English Tarbiyah Faculty during the new normal Covid-19 pandemic at Fatmawati Sukarno Bengkulu State Islamic University in 2021-2022. This qualitative research aims to describe and analyse the ability, form, uniqueness, and variety of strategies produced by English lecturers in the classroom. The results of this study indicate that there are several strategies used by English lecturers, especially in facilitating student interactional communication. The strategies are providing a new learning environment with students, providing two-way communication with students, facilitating communication media between students (student peer feedback), and activating role play models in the classroom and contextual teaching processes. Several obstacles to facilitating student interactional communication at Fatmawati Sukarno Bengkulu State Islamic University include limited teaching time due to social distance, the learning process is only 60% offline and 40% online so that face-to-face learning is not optimal. English lecturers can improve their teaching competence through several online trainings, online seminars, and online workshops. In fact, the results of the research, it can be concluded that the strategy in facilitating student English interactional communication is very important to be applied in the English class to achieve the aims and objectives of teaching English.